What is the importance of open habitat in a predominantly closed forest area to the dung beetle (Coleoptera, Scarabaeinae) assemblage? - Costa,Fábio C. (2013)
What is the importance of open habitat in a predominantly closed forest to the dung beetle assemblage? The Atlantic Forest in Brazil is one of the most highly disturbed ecosystems and is mainly represented by fragmented areas. However, in places where human disturbances have ceased, certain areas are showing a natural regeneration pattern. The aim of the present study was to determine how the dung beetle assemblage responds to distinct habitat structures in a fragment of Atlantic Forest. For such, open and closed forest areas were sampled in a fragment of the Atlantic Forest in the northeastern region of Brazil. Pitfall traps baited with excrement and carrion were used to collect the beetles. A total of 7,267 individuals belonging to 35 species were captured. Canthon chalybaeus and C. mutabilis were restricted to open areas. Nearly 90% of the individuals of C. aff. simulans and Deltochilum aff. irroratum were identified in these areas. A higher percentage (> 50%) of Canthon staigi, Dichotomius aff. depressicolis and D. aff. sericeus occurred in closed areas. Abundance differed between areas, with higher values in closed areas. Richness was not influenced by the habitat structure. NMDS ordination exhibited the segregation of areas and ANOSIM confirmed that this variable explained the assemblage of dung beetle species. The findings of the present study validate that open areas are associated to more restrictive conditions, limiting a higher abundance of dung beetle. Although situated near preserved fragments, the studied open areas increase the heterogeneity of the general landscape.